Cytotoxic Analysis Of Christia Vespertilionis Leaves Extracts Treated On Human Cervical Cancer Cell (Hela) - Sidek, Mohammad Mizwaruddin (2019)
Plants have been used by old folk for many therapeutic effect long time ago. In modern age, the popularity of using plants especially for anticancer activities has kept increasing. Many studies have been conducted to extracted out all phytochemical compound contained in the plant who might be responsible for therapeutic effects such as anticancer activities. Plus, many testimony of herbal supplements as cancer treatment has been conducted without any scientific evidence. In this study, Christia vespertilionis leaves extracts have been used to investigate the cytotoxic activities of the plants towards cancer cell line. C. vespertilionis leaves have been fraction using partition extraction from crude (methanol) extract followed by partitioning extract with increasing polarity namely hexane, dichloromethane, chloroform, n-butanol and aqueous fractions. From the findings, dichloromethane (DCM) extract of C. vespertilionis leaves has shown the highest cytotoxicity properties in human cervical cancer cell line (HeLa) indicated by half inhibitory concentration (IC50). DCM fraction exhibited significant cytotoxicity with IC50 value of 63.68, 55.42 and 53.04 μg/mL at 24, 48 and 72 hours respectively. The present of apoptotic bodies and considerable percentage of cell to detach in 24 hours exposure might suggest cytotoxicity effect of the extract. Plus, the presence of various phytochemical compounds in the extract using gas chromatography-mass spectrometry such as 9,12,15-octadecatrienoic acid, methyl ester, (Z, Z, Z)-, hexadecanoic acid, methyl ester, phytol, cyclododecane, and 2-propenoic acid might be the reason for the cytotoxic and anti-proliferative activity exhibited by extracts onto the HeLa cell lines. It was suggested that this plant might has pharmacological importance in the future.